THE INFLUENCE OF THE LEADERSHIP STYLE OF SCHOOL PRINCIPALS ON THE TEACHERS’ HAPPINESS AND MOTIVATION IN ISRAELI ARAB SCHOOLS - Loureen HADDAD; Nicolae BIBU (Oradea Journal of Business and Economics, 2025)
This paper examines the influence of the leadership styles (transformational, transactional, laissez-faire) used by school principals on the happiness, motivation and job satisfaction of teachers in Arab schools in Israel. The article presents the findings of a quantitative analysis, where the impact of the leadership styles was examined. The data was obtained using a questionnaire that was distributed to teachers. The findings show that transformational and transactional leadership style have a low influence on the happiness of teachers, and a strong influence on the motivation of teachers in Arab schools. Their use by school principals enhances the development of collaborative relations between teachers at school, and thus increases their job satisfaction, too. The authors recommend to school principals to learn and practice a mix of leadership styles, such as transformational, transactional, collaborative and empowering is formulated.